Status of NSLS-II booster - Gurov, S.M.; Akimov, A.V.; Anchugov, O.V.; Batrakov, A.M.; Belikov, O.V.; Bekhtenev, E.A.; Burenkov, D.B.; Cheblakov, P.B.; Cherepanov, V.P.; Chernyakin, A.D.; Cheskidov, V.G.; Churkin, I.N.; et al. (Вопросы атомной науки и техники, 2012)
The National Synchrotron Light Source II is a third generation light source under construction at Brookhaven National Laboratory. The project includes a highly optimized 3 GeV electron storage ring, linac pre-injector and full-energy booster-synchrotron. Budker Institute of Nuclear Physics builds booster for NSLS-II. The booster should accelerate the electron beam continuously and reliably from minimal 170 MeV injection energy to maximal energy of 3.15 GeV and average beam current of 20 mA. The booster shall be capable of multi-bunch and single bunch operation. This paper summarizes the status of NSLS-II booster.